2012
DOI: 10.1200/jco.2012.30.15_suppl.4034
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a phase I/II study in patients with pancreatic cancer, malignant melanoma, and colorectal carcinoma with trabedersen.

Abstract: 4034 Background: TGF-β2 overexpression in solid tumors triggers key cancer pathomechanisms, i.e. suppression of antitumor immune responses system and metastasis. Trabedersen specifically inhibits TGF-β2 expression. In the clinical Phase I/II study we evaluate MTD, safety, pharmakokinetics (PK), and efficacy of i.v. trabedersen in patients with advanced tumors. Methods: A total of 61 patients with pancreatic cancer (PancCa, n=37), malignant melanoma (MM, n=19), or colorectal carcinoma (n=5) were treated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…A role for TGF-β2 in supporting the invasive potential of 6.5/ cancer cells was next evaluated using Trabedersen, a specific TGF-β2-targeting antisense oligonucleotide currently evaluated in clinical trials [38][39][40] , and SB431542, a selective TGF-βRI inhibitor. We first documented that Trabedersen reduced TGF-β2 mRNA and protein expression ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for TGF-β2 in supporting the invasive potential of 6.5/ cancer cells was next evaluated using Trabedersen, a specific TGF-β2-targeting antisense oligonucleotide currently evaluated in clinical trials [38][39][40] , and SB431542, a selective TGF-βRI inhibitor. We first documented that Trabedersen reduced TGF-β2 mRNA and protein expression ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we documented the druggability of this intrinsic alteration of the cancer cell phenotype with SB431542, a potent and specific inhibitor of TGF-β superfamily type 1 receptor, and AP12009/Trabedersen, a FDA-and EMEA-approved orphan anticancer drug, active as a TGF-β2-specific antisense oligodeoxynucleotide. While TGF-β2 was identified as an attractive target to block oncogenesis resulting from stem cell renewal 62 and encouraging survival results have been reported with Trabedersen in gliomas 38 and pancreatic cancers 39,40 , inhibitors of TGF-β2 signaling may actually represent a therapeutic strategy with a broader potential of reducing metastatic burden. Potential therapeutic targets may also be derived from the observation that LD represent a nondispensable source of fuels to support anoikis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It was also successfully tested in an open label Phase I/II study in patients with stage III/IV pancreatic cancer, malignant melanoma, and colorectal cancer (CRC). 156 Results showed that the drug was safe and well tolerated even if some patients developed thrombocytopenia. Furthermore, in one pancreatic cancer patient there was a complete response of liver metastases to the treatment and, at that time, he was still alive after 75 months.…”
Section: Inhibiting the Tgf-β Signaling Pathwaymentioning
confidence: 96%
“…In cancer, inhibition of TGF-βsignaling targets the tumor microenvironment to prevent progression via multiple mechanisms including inhibiting metastasis and reducing immunosuppression. Hepatocellular carcinoma (HCC), renal cell carcinoma, melanoma, glioblastoma, pancreatic carcinoma, and breast cancer are tumor types that are currently being evaluated for treatment with TGF-β-signaling inhibitors (9)(10)(11)(12)(13)(14). Fibrosis of tissues such as lungs, heart, and kidneys is also associated with increased TGF-β-signaling, likely due to excess ligand availability (15).…”
mentioning
confidence: 99%